Government Policy in Community Waste Management: A Case Study of Waste Management in Subang Regency - Latifah Latifah; Fatmawati Fatmawati; Ilham Ilham; Abd Gafur; Purnomo Yustianto (Jurnal Public Policy, 2023)
Waste management must start from the initial waste disposal site, both at household, institutional and temporary disposal sites. The involvement of shareholders is very much needed in waste operational activities, because they have their respective duties which include starting from the stages of taking, processing, then final disposal, and utilizing waste. Likewise, the government certainly has other ways of controlling waste by involving the participation of the community. Because the role of the government is very crucial, it can be in the form of direct assignments to the community through the relevant agencies, or in the process of enforcing the rules that have been applied. The research used is a qualitative-interpretative descriptive method with a phenomenological approach as an exploration in the application of the e-performance system to government employees in Subang district. This study focuses on the Subang Regency government's policy in managing community waste. The purpose of this study is to measure the extent to which the Subang Regency Government implements policies related to waste management. 5 of 2018 has not run optimally, the availability of facilities and infrastructure such as government-owned waste banks so that the management of waste services is still low, then socialization has not been maximized so that people lack awareness in disposing of waste.